Crangonyx islandicus N & Kristjánsson, 2006, sp. nov. ... - N, Jörundur Svava R S S O; Kristjánsson, Bjarni K. (Zenodo, 2006)
Crangonyx islandicus sp. nov. (Figs 1–6) Material examined Holotype. Female, 6.8 mm, non-ovigerous, brood plates with setae, Vatnsvik, 64°14.46´N, 21°03.19´W, Thingvallavatn, Southwest Iceland, 12 July 2001, groundwater inflow to the lake, 4°C, 30 ppm conductivity, electric fishing, coll. B.K. Kristjánsson, IMNH 2164. Paratypes. Vatnsvik, 64°14.46´N, 21°03.19´W, Thingvallavatn, Southwest Iceland, 8 May 2001, 21 specimens (drawn paratype included), groundwater inflow to the lake, electric fishing, coll. B.K. Kristjánsson, IMNH 2165; Vatnsvik, 64°14.46´N, 21°03.19´W, Thingvallavatn, Southwest Iceland, 12 July 2001, 7 specimens, groundwater inflow to the lake, electric fishing, coll. B.K. Kristjánsson, IMNH 2166; Nautavakir, 64°00.876´N, 20°53.018´W, Southwest Iceland, 1 August 2003, 6°C, 60 ppm conductivity, coll. B.K. Kristjánsson & J. Svavarsson, 1 specimen, IMNH 2167. Other material examined Vatnsvik (64°14.46´N, 21°03.19´W), Thingvallavatn, Southwest Iceland, electric fishing, coll. B.K. Kristjánsson: ... : Published as part of N, Jörundur Svava R S S O & Kristjánsson, Bjarni K., 2006, Crangonyx islandicus sp. nov., a subterranean freshwater amphipod (Crustacea, Amphipoda, Crangonyctidae) from springs in lava fields in Iceland, pp. 1-17 in Zootaxa 1365 on pages 2-13, DOI: 10.5281/zenodo.174801 ...